Implications of the energy transition for government revenues, energy imports and employment: The case of electric vehicles in India. (April 2023) - Rajagopal, Deepak
Abstract: Whereas the environmental benefits of transitioning away from fossil fuels are becoming indisputable, the implications for government revenues, employment, balance of trade, and employment appear less clear. Using an accounting-like framework, we analyze the potential near to medium-term implications of electric vehicles displacing internal combustion engine (ICE) vehicles. Total cost of ownership (TCO), imports, government revenues, employment and greenhouse gas (GHG) emissions are each lower with EVs under different market and policy scenarios considered. An exception is a steep fall in oil prices (say by 50% from current levels), which increases net energy imports when battery cells are imported. Targeting high usage vehicles for EV adoption amplifies reduction in TCO, GHG emissions and imports but also leads to greater reduction in tax revenues. Furthermore, foregone tax revenues from avoided fossil fuel consumption is several times greater than the subsidies to EVs in the form of preferential tax rates. On a per vehicle basis, each fossil fuel vehicle generates over six-fold greater taxes over its life relative to an EV. Whereas economic growth and public policy can mitigate adverse impacts on government revenues and employment, simultaneously reducing total emissions as well will, if history is a guide, be more challenging. Highlights: EVs and ICE vehicles are compared based on multiple criteria Life cycle cost, imports, tax revenues, jobs, emissions are each lower with EVs Tax revenues from fossil fuels amount to over 10% of Indian government expenditure Each ICE vehicle generates over 6X greater taxes over its life relative to an EV Carbon tax can help offset but a portion of the losses in fuel tax revenues